Risk Perception and Needs: Defining Extension's Climate Change Adaptation Role - Mark Megalos; Martha Monroe; Claire Needham Bode (EDIS)
Third in a series on climate change communication for Extension professionals, this 7-page fact sheet provides strategies for overcoming challenges in communicating about climate change. Written by Mark Megalos, Martha C. Monroe, and Claire Needham Bode, and published by the UF School of Forest Resources and Conservation, April 2016.